Customer Loyalty in Low-Cost Carriers: the Role of Service Quality, Price Fairness, and Brand Image (Insights from Indonesia) - Anggreana Vera Salsabila; Karto Adiwijaya (Green Publisher Indonesia, 2025)
This study aims to analyze the effect of service quality, price fairness, customer satisfaction, and trust on customer loyalty, with brand image as a moderating variable, on low-cost carrier (LCC) airlines in Indonesia. The LCC industry faces tough challenges, with fluctuations in demand and the need to keep prices affordable without sacrificing service quality. Therefore, price fairness and brand image are key in increasing customer satisfaction, trust and loyalty. This study uses a quantitative approach with descriptive and causal designs, and a structured survey of LCC airline customers. Data were analyzed using PLS-SEM (Partial Least Squares Structural Equation Modeling), which includes service quality dimensions (reliability, tangible, assurance, empathy), price fairness, customer satisfaction, trust, and its effect on customer loyalty. The results showed that service quality has a positive effect on price fairness and customer satisfaction, but not directly on customer loyalty. Price fairness proves to be important to encourage customer satisfaction and customer loyalty, while customer satisfaction acts as a mediator in the relationship, and has a direct effect on trust and customer loyalty. Trust contributes significantly to building customer loyalty. However, brand image does not moderate the relationship between service quality and price fairness, suggesting that LCC customers' decisions are based more on functional evaluation. The findings make theoretical and practical contributions to improving service quality and creating a satisfying customer experience.